A pilot study on fear and risk of fall: The impact of an8-month multicomponent exercise program in community-dwelling aged adults - Rodrigues, Filipe (2023)
The objective of this study was to investigate the impact of an 8-month multicomponent exercise program in community-dwelling older adults. A comprehensive approach was employed to assess the feasibility and effectiveness of a thrice-weekly exercise intervention. Aged over 60 years, the capacity to stand and walk with or without assistive equipment, being physically inactive, medical clearance, and living in the community were all eligibility criteria. The Timed-up and Go test and Berg Balance Scale were used to examine risk of falling. The Fall-Efficacy Scale International was used to examine the fear of falling. The community-based exercise program involved thirty-five participants, the average age was 67.54 years (SD = 3.81) and 71% were female. At-tendance rates ranged from 76% to 100% on average. There was a significant trend toward a clinically important improvement in the timed-up and go test (t = 4.66; p < .001; d = 0.20), berg balance scale (t = -11.20; p < .001; d = 1.47) and fall-efficacy scale international (t = 5.81; p < .001; d = 0.88). This study has provided preliminary evidence that an 8-month community-based low-cost exercise program may be effective in improving agility, balance, and decreasing fear of falling in older people.